PENGARUH METODE DONGENG TERHADAP HASIL DAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Nurrosyida, Erlin; Julia, Julia; Syahid, Aah Ahmad (Jurnal Pena Ilmiah, 2017)
This study was designed to create different atmosphere on learning illustration drawing for primary school students. The method was through fairy tales before students begin to draw. This research used quasi-experimental design with nonequivalent control group. The sample was 5th grade primary school students in SDN Sukalilah, reflected the population of all 5th grade primary school students in Pamulihan subdistrict. Analyzed using significant poin at 0.05 or 5%, results showed that learning through fairy tales method contributed significantly to students result of animal and its nature illustration drawing, with determinant percent 45,02%. In addition, using Fairy Methode could increase the Learning Motivation of the students, yet, not significantly. There are positive relations between the Learning Drawing result by Learning Motivation of student for about 0,25%.